Characteristics in Molecular Vibrational Frequency Patterns between Agonists and Antagonists of Histamine Receptors - S. June Oh (Genomics & Informatics)
To learn the differences between the structure-activity relationship and molecular vibration-activity relationship in the ligand-receptor interaction of the histamine receptor, 47 ligands of the histamine receptor were analyzed by structural similarity and molecular vibrational frequency patterns. The radial tree that was produced by clustering analysis of molecular vibrational frequency patterns shows its potential for the functional classification of histamine receptor ligands.